A new approach to understand the Cassie state of liquids on superamphiphobic materials. Issue 5 (19th January 2016) - Wang, Tao; Cui, Jing; Ouyang, Shenshen; Cui, Weihao; Wang, Sheng
Abstract : A hierarchical structure is a prerequisite for a liquid super-repellent surface due to its capability to catch large numbers of fine air-pockets. Abstract : A hierarchical structure is a prerequisite for a liquid super-repellent surface due to its capability to catch large numbers of fine air-pockets. In the present work, a series of hierarchical nanocomposites with anti-wettability were fabricated by in situ deposition of spherical SiO2 nanoparticles on Te@C nanofibers. N2 adsorption–desorption isotherms were used for the first time to characterize the air-pockets and relate them to the wettability of the nanocomposites. The results indicate that superamphiphobicity is a contribution of a delicate synergistic effect between a micro-scale structure and a nano-scale structure. Significant dominance of either of them led to reduced superamphiphobicity. The superamphiphobic "beads on a string" materials should meet the following features: higher S BET that ensures enough air-pockets ( S BET value of the superamphiphobic sample is much higher than that of the superhydrophobic one); and the most important, a "continuous and balanced" distribution of micro and macro air-pockets derived from hierarchical structures.